METODE PELAKSANAAN ERECTION BAJA MENGGUNAKAN MOBILE CRANE PROYEK RENOVASI GERBANG DAN PLASA TOL TEMBALANG â SEMARANG PT. JASA MARGA - , ADI SUPRIANTO; , Agus Kurniawan, ST.,MT.,Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Along with the increasing volume of vehicles to the location Tembalang Toll Plaza and inadequate Toll Plaza then Jasa Marga as the manager of highway which includes the toll booths Tembalang toll plaza renovation, remodeling toll gates, and the addition of a counter. In the implementation of the Project Renovation and Plaza Toll Gate Tembalang, one of which was about the method where steel erection work on the steel erection work has a pretty interesting design is modeled as an open frame structure (Structure bearers order moments) and 3-dimensional truss. Where the structure consists of the framework composed of beams and columns and bracing steel I / WF supporting the wind load, billboards, workers live loads, lighting, ME, and the pile is modeled as a joint behave as anchor connected to the main structure, and implementation is carried out night so as not to disrupt the flow of traffic passing through the toll road.